Trajetória de Núbia Nascimento Marques : contribuições para a educação em Sergipe (1978-1999) - Melnikoff, Elaine Almeida Aires (2014)
This study aims to analyze the trajectory of teacher Nubia Birth Marques , investigating their contributions to education in Sergipe . It also seeks to highlight the woman intellectual , writer , teacher , poet , and his work as a pioneer in Sergipana Academy of Letters ( ASL ) . The time frame covers the period from 1978, the year of entry into the ASL , 1999, the year of his death . The sources were located inside the Library , Federal University of Sergipe , in the General Archives of the Federal University of Sergipe , records in newspapers of the Institute of History and Geography of Sergipe and the Social Service Department of the Federal University of Sergipe . The theoretical-methodological procedures adopted are linked to the assumptions of Cultural History and Biographical Approach . The main categories of analysis are mobilized : Social Capital , Cultural Capital , Bourdieu´s Masculine Domination (1998 ) ; intellectual Sirinelli ( 2003). Nubia Birth Marques was one Agent cultural active woman bound in culture and education . Thus , this study intend to investigate the performance of this character in the educational setting and understand the contributions to the history of education in Sergipe .